ChemInform Abstract: Comparative in Operando Studies in Heterogeneous Catalysis: Atomic and Electronic Structural Features in the Hydrogenation of Ethylene over Supported Pd and Pt Catalysts. Issue 19 (May 2015) - Jung, Ulrich; Elsen, Annika; Li, Yuanyuan; Smith, Jeremy G.; Small, Matthew W.; Stach, Eric A.; Frenkel, Anatoly I.; Nuzzo, Ralph G.
Abstract Review: 111 refs.